Online information seeking behavior of Facebook's "Free Data" users in Barangay San Manuel and Barangay Citrus in San Jose Del Monte, Bulacan - Bunao, Jessie Angeli B. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
In 2015, free data was introduced when Facebook came to a partnership with Philippines mobile carrier to launch Free Basics and internet org. Both the application and the website gave Filipinos free data access to online services related to education, health, news, etc. Some Filipinos are aware of free data and its usage but in a generation where having a mobile phone is part of one’s everyday living, it is important to reach a point further than awareness. Filipinos who are part of the younger generation are most often connected through social media.